2022
DOI: 10.18632/aging.203997
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-29 aggravates myocardial infarction via inhibiting the PI3K/mTOR/HIF1α/VEGF pathway

Abstract: Introduction: MI is defined by the presence of myocardial necrosis, which is caused by acute and persistent ischemia and hypoxia of the coronary artery. In recent years, its incidence rate has been on the rise in China. Methods: GSE34198, GSE97320 and GSE141512 datasets were download for DEG analysis. KEGG pathway analysis, GO analysis, GSEA and PPI network construction were performed. Later, target genes of candidate miRNAs were predicted. Next, echocardiography was conducted to detect the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…All of these suggesting that AKT molecule converges multiple signals to regulate macrophage pro-and antiin ammatory effects. The role of PI3K/AKT/mTOR signaling pathway in myocardial infarction including regulation of macrophage phenotypic transformation [25], autophagy [26] and angiogenesis [27]. Our results investigated that Desoxyrhaponticin inhibited macrophages M1 polarization by downregulating PI3K/AKT/mTOR signaling pathway.…”
Section: Discussionmentioning
confidence: 90%
“…All of these suggesting that AKT molecule converges multiple signals to regulate macrophage pro-and antiin ammatory effects. The role of PI3K/AKT/mTOR signaling pathway in myocardial infarction including regulation of macrophage phenotypic transformation [25], autophagy [26] and angiogenesis [27]. Our results investigated that Desoxyrhaponticin inhibited macrophages M1 polarization by downregulating PI3K/AKT/mTOR signaling pathway.…”
Section: Discussionmentioning
confidence: 90%
“…Wang et al [ 44 ] investigated the role of miR-22 and miR-499 as sensitive biomarkers in the diagnosis of MI, confirming that these miRNAs could play an important role in early diagnosis. Wang et al [ 77 ] investigated the role of miR-29: it was expressed less in subjects after MI. These authors demonstrated that the inhibition of this miRNA promoted angiogenesis, reduced fibrosis, and alleviated MI damage.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, polarization of HAE may also play a protective role through VEGF induction of angiogenesis. Wang et al [16] also show that injection of muscone in mice increases angiogenesis around the infarct area, as well as increased phosphorylated VEGF Receptor (P-VEGFR2) in vascular endothelial cells. Western blot and PCR results show increased expression of HIF-1α and VEGF, which proves that muscone can protect myocardial infarction by up-regulating VEGF through HIF-1α.…”
Section: Hypoxia Activates Downstream Genes Of Hif-1α In Ihdmentioning
confidence: 94%
“…miR-29 works by increasing the contractile load of cardiac myocytes and results in more serious disease, and it can combine with PI3K so that, it can initiate the phosphorylation pathway which leads to PI3K to degrade. In other words, after the use of inhibitors, PI3K/mTOR/HIF-1α/VEGF pathway can be activated and the increase of the VEGF expression promotes and improves the function of myocardial cell [16] . Gonzalez-king et al [15] show that injection of Hydroxyapatite Electret (HAE) into mice can significantly reduce myocardial infarction area and fibrosis in the distal unaffected area is also significantly reduced.…”
Section: Hypoxia Activates Downstream Genes Of Hif-1α In Ihdmentioning
confidence: 99%